Error analysis of narrative writing among secondary school students in Selangor, Malaysia - Mehat, Siti Zawani; Ismail, Lilliati; Noordin, Nooreen; Mohamad Ali, Afida (Human Resource Management Academic Research Society, 2024)
Writing complexity is a significant challenge for ESL students since students are pressured to master a variety of linguistics skills, grammar, syntax, and vocabulary. For students to develop a strong command of English in writing, they must be able to integrate these skills effectively, which can be a daunting task. This issue is increasingly recognised by educators and researchers, highlighting the need for targeted interventions to address the complex challenges of writing in a second language. Employing the Error Analysis framework (Corder & Brown, 1988), this study aims to determine the frequent errors in narrative writing among secondary school students. The research design chosen for this study is a quantitative content analysis of the student’s narrative writing corpora. Data collection involved 52 writing samples of secondary school students with varying levels of English proficiency, ranging from beginner to intermediate. Students’ corpora were marked, tagged, and analysed based on surface and linguistics taxonomies (Dulay,1982) using the TagAnt and Antconc software. The findings show that the most common errors were related to grammar (42.64%), followed by omission (18.29%), morphology (12.51%), lexical issues (12.22%), addition (6.35%), misformation (3.85%), semantics (2.40%), and misordering (1.64%). The results and discussion suggest that students frequently make errors in the application of grammar rules and the omission of function words in sentences, indicating a need for targeted assistance in these areas of language learning.